EARTHWORM ECOLOGY, HEAVY METALS AND TOTAL PETROLEUM HYDROCARBON ASSESSMENT OF AN OIL SPILL SITE IN AGAYE, LAGOS STATE, NIGERIA. (2014)
Agaye has experienced frequent spills of premium motor spirit due to pipeline vandalization. Over time,the spills have contaminated the water sources and farmlands, and with the attendant inferno, destroyed the soil biota. There is dearth of scientific information on effect of the spills in this area. This study investigated the abundance and heavy metals level of earthworm, and determined the physico-chemical parameters of the groundwater, surface-water and soil in Agaye. Twenty topsoil samples (0.5m x 0.5m x 0.2m) were randomly collected monthly within the epicenter of the spill and 500 meters away from the spill between June 2007 and April 2009 for earthworm analysis. The earthworms were handpicked, identified with standard keys and counted. Cadmium, Copper, Nickel, Zinc, Manganese and Lead concentrations in tissue of the two most abundant earthworm species were determined using atomic absorption spectrophotometry. Seven existing water sources (GW1 to GW5 for groundwater; SW1 and SW2 for surface-water) were sampled along the transect of spill. Soil samples (S1-S5) were collected around same loci of the groundwater sites. GW6 and S6 served as control, being 500m away from spill. Samples collected every two months were analysed for pH, Total Petroleum Hydrocarbon (TPH) and the heavy metals according to APHA, 1995. Earthworm diversity and abundance were analysed using Shannon Weiner (HS) and Mann-Whitney respectively while data on physicochemical parameters were analysed with ANOVA at p=0.05. In the first 12 months, Lybiodrilus violaceous was the only earthworm encountered within the epicenter while L. violaceous and Dichogaster modigliani (H = 0.3) were found 500m away. In the last 11 months, L. violaceous, D. modigliani, Ephyriodrilus afroccidentalis and Heliodrilus lagosensis were encountered in both sites (H = 0.3, at the epicenter; H = 0.9, 500 m away). The abundance of earthworm 500m away (204 earthworms/m2) was significantly higher than within the epicenter (45 earthworms/m2) in the first 12 months but not significantly different in the last 11 months. The concentration (?g/g) of Lead, Cadmium, Copper, Zinc and Manganese in L. violaceous was 0.4±0.02, 0.2±0.003, 0.1±0.003, 5.5±0.02 and 3.7±0.002 respectively; Nickel was not detected. Only zinc (6.7±0.4) and Cadmium (0.06±0.002) were detected in D. modigliani. Cadmium (0.0±0.1 mg/L) and Nickel (0.1-1.6 mg/L) levels in GW1 to GW5 were higher than control (GW6) and NESREA drinking water limits. Cadmium, Copper and Nickel levels (mg/L) in SW1 and SW2, (ranged 0.0-0.1, 0.07-0.7 and 1.5-2.8 respectively) were higher than NESREA permissible limit. Mean concentrations of TPH were significantly higher in surface-water (3.3±0.5 mg/L) than groundwater (1.3±0.6 mg/L) while pH was significantly lower in groundwater than surface-water. Mean pH at S1-S5 ranged from 5.3±0.04 to 6.5±0.02. Soil TPH, cadmium and copper reduced significantly during the last 11 months. Soil TPH level was significantly higher than control soil. The increase in number and species of earthworm in the last 11 months indicated possible remediation of the environment. The high concentrations of heavy metals in the earthworms suggest possible roles in bioaccumulation. The higher levels of heavy metals and total petroleum hydrocarbon in surface and groundwater indicated that they are unsafe for drinking.